Quality and grain yield of barley (Hordeum vulgare L.) as influenced by nitrogen application at different growth stages - Bikramjeet Singh; A. S. Sidhu; Kuldip Singh; Jagdish Singh (Annals of Agricultural Research, 2025)
Nitrogen availability is most important factor, known to influence the yield and quality of barley. Therefore, present investigation was undertaken, with the objective of studying the effect of different levels and time of nitrogen (N) application on protein, malt content and yield of barley, during rabi season of 2017–2018. The Bathinda and Ludhiana districts of Punjab hosted the field experiment, which comprised of three N levels (N1- 46 , N2- 62 , N3- 77 kg N ha-1) and four times of their application (T1- Full dose at pre-sowing irrigation, T2- ½ N at pre-sowing irrigation + ½ tillering stage, T3- ½ N at pre-sowing irrigation + ¼ tillering stage + ¼ stem elongation and T4- ½ N at pre-sowing irrigation + ¼ tillering stage + ¼ flowering stage). Grain yield and protein content were significantly higher under application of 77 kg N ha-1 (N3), but it was statistically at par with 62 kg N ha-1 (N2) when both the doses were applied in two equal fractions at pre sowing irrigation and tillering stage. The split application (T2) of N increased the grain yield of barley by 25.8% and 38.4% at Bathinda and Ludhiana, respectively. Like grain yield, protein content significantly increased by 24.5% and 17.8% at Bathinda and Ludhiana respectively, with split N application at pre sowing irrigation, tillering and flowering stages (T4) as compared to T1 treatment, but was statistically at par with T2 and T3 treatments. Malt content showed opposite trend, the good malt characteristics were obtained with 46 kg N ha-1 (N1) applied fully at pre sowing irrigation (T1). It means that for obtaining good malt characteristics, application of full N at pre sowing irrigation is better over split N application. Grain yield and protein content (%) showed positive and linear relationship with total N uptake while hot water extract (%) showed negative and linear relationship.